Collegiate and professional ice hockey athletic trainers` hydration practices and knowledge: Part 2 - Emerson, D. M.; Torres-McGehee, T. M.; Yeargin, S. W.; Dolan, K.; deWeber, K. K. (International Journal of Athletic Therapy & Training, 2020)
An athletic trainer`s (ATs) role requires current knowledge about factors that can influence hydration status. The purpose of this study was to determine awareness of alcohol and caffeine effects on hydration. Participants were 94 ATs with NCAA Division I or III men`s and/or women`s ice hockey teams and 82 head ATs with professional ice hockey teams. The majority of ATs were correct regarding alcohol`s effects on hydration, specifically knowing alcohol increases urine output (92.1%), delays fluid recovery (81.7%), and dehydrates a euhydrated individual (83.5%). In contrast, fewer ATs were correct that moderate, regular consumption of caffeine does not cause dehydration (20.7%), delay fluid recovery (15.2%), or impair fluid regulatory hormones (9.8%). While ATs were knowledgeable about alcohol effects, there remains misconceptions about caffeine on hydration.